La lluvia y el transporte de nutrimentos dentro de ecosistemas de bosques y cafetales - Jaramillo Robledo, A.
(Es)
ilus., 35 ref.
Keywords: COFFEA ARABICA; CORDIA ALLIODORA; PINUS OOCARPA; EUCALYPTUS GRANDIS; BALANCE HIDRICO; ESCORRENTIA; LIXIVIACION; NUTRIENTES; COLOMBIA; INTERCEPTACION